2019
DOI: 10.1016/j.cell.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

CerS6-Derived Sphingolipids Interact with Mff and Promote Mitochondrial Fragmentation in Obesity

Abstract: Highlights d CerS6, but not CerS5, deficiency protects from obesityassociated insulin resistance d CerS6, but not CerS5, regulates C 16:0 ceramides in mitochondria and MAMs d CerS6-derived C 16:0 sphingolipids interact with Mff d CerS6 and Mff regulate mitochondrial dynamics and insulin resistance in obesity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
233
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(242 citation statements)
references
References 70 publications
8
233
1
Order By: Relevance
“…Previous publications implicated CerS5 and CerS6 in obesity and glucose intolerance (Gosejacob et al, ; Hammerschmidt et al, ). We, therefore, scrutinized the data for possible co‐founding effects of body mass index (BMI) and type 2 diabetes.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous publications implicated CerS5 and CerS6 in obesity and glucose intolerance (Gosejacob et al, ; Hammerschmidt et al, ). We, therefore, scrutinized the data for possible co‐founding effects of body mass index (BMI) and type 2 diabetes.…”
Section: Resultsmentioning
confidence: 87%
“…As a metabolic organ, skeletal muscle is closely linked to glucose homeostasis. Indeed, previous publications implicated CerS1 and CerS5 in obesity and glucose intolerance (Hammerschmidt et al, ; Turpin et al, ; Turpin‐Nolan et al, ) (Gosejacob et al, ) Specifically, CerS1‐derived C18‐ceramide in skeletal muscle was shown to enhance whole‐body glucose metabolism in obesity by increasing the muscle‐derived adipokine Fgf21 (Turpin‐Nolan et al, ). The impact of CerS5 is controversial.…”
Section: Discussionmentioning
confidence: 94%
“…In this context, lowering cellular ceramide by ablating dihydroceramide desaturase 1 increased mitochondrial oxygen flux and improved steatosis and glucose metabolism in insulin-resistant mice 63 . Conversely, mitochondrial C16:0 ceramide, generated by overexpression of ceramide synthase 6 (CerS6), interacts with mitochondrial fission factor (MFF) to promote mitochondrial fragmentation, insulin resistance and steatosis 64 . Silencing of MFF prevented CerS6-dependent metabolic abnormalities despite elevated C16:0 ceramide.…”
Section: Reviewmentioning
confidence: 99%
“…Of these, CerS5 and CerS6 add SFA C 16:0 to the sphingoid backbone. Liver‐specific CerS6, but not CerS5, knockout mice are protected against SFA‐induced IR and steatosis . This difference was recently attributed to the ability of CerS6‐derived sphingolipids to bind mitochondrial fission factors and promote FA‐induced mitochondrial fragmentation on subcellular pools of C 16:0 ceramides …”
mentioning
confidence: 99%
“…Liver-specific CerS6, but not CerS5, knockout mice are protected against SFA-induced IR and steatosis. (6,7) This difference was recently attributed to the ability of CerS6-derived sphingolipids to bind mitochondrial fission factors and promote FA-induced mitochondrial fragmentation on subcellular pools of C 16:0 ceramides. (7) The final step of ceramide formation involves insertion of a single double bond to dihydroceramide (DH-Cer) by the enzyme dihydroceramide desaturase 1 (DEGS1).…”
mentioning
confidence: 99%